2020
DOI: 10.1016/j.ijdrr.2020.101657
|View full text |Cite
|
Sign up to set email alerts
|

Simulating emergencies with transport outcomes Sim (SETOSim): Application of an agent-based decision support tool to community evacuation planning

Abstract: In the time since the 2004 Indian Ocean tsunami and Hurricane Katrina in 2005, an increasing number of studies have focused on developing agent-based simulations of citizen evacuation behaviours. The application of simulation to practice (i.e. evacuation planning, community disaster risk reduction strategy), however, is limited. This research aims to explore the effective application of agent-based evacuation simulation to better inform community evacuation planning through a collaborative process. The study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Only 5 of the 53 papers were accompanied by source code (Aguilar et al 2017 ; Nakanishi et al 2020 ; Naqvi 2017 ; Slucki and Nielek 2015 ; Wijerathne et al 2013 ) and only one pseudocode (Poulos et al 2018 ) was found. This means that approximately 90% of the models are virtually impossible to replicate and the published results cannot therefore be at least quantitatively verified.…”
Section: Technical Properties Of Abm Modelsmentioning
confidence: 99%
“…Only 5 of the 53 papers were accompanied by source code (Aguilar et al 2017 ; Nakanishi et al 2020 ; Naqvi 2017 ; Slucki and Nielek 2015 ; Wijerathne et al 2013 ) and only one pseudocode (Poulos et al 2018 ) was found. This means that approximately 90% of the models are virtually impossible to replicate and the published results cannot therefore be at least quantitatively verified.…”
Section: Technical Properties Of Abm Modelsmentioning
confidence: 99%
“…The definition of tools able to assist a community in making local decisions during an evacuation reveals essential in order to improve the emergency planning. The relationship between users' behavior during an evacuation and individual perceptions of risk has a certain scientific rationality, and agent-based models taking into account alternative evacuation plans based on the understanding of residents' movements according to changes of environment, [49], as well as analyzing the effect of disaster risk perception on various emergency behaviors related to one's own perceived vulnerability, [50], have been proposed.…”
Section: A State Of the Artmentioning
confidence: 99%
“…For instance, an agent senses flood risk when the floodwater level exceeds building heights. In an example of endogenous sensing by Nakanishi et al (2020), agents observe their surrounding environment, updating their knowledge of the relative safety of different locations. Moreover, individuals sense a flood warning issued by the local authority and sense an impending flood at a distance of 100m (Alonso Vicario et al 2020).…”
Section: Sensingmentioning
confidence: 99%
“…Alonso Vicario et al (2020) used different probabilities to add randomness in daily routines and behavioural parameters. Nakanishi et al (2020), also incorporated stochasticity, where agents probabilistically adjust their willingness to evacuate based.…”
Section: Stochasticitymentioning
confidence: 99%
See 1 more Smart Citation